2001
DOI: 10.2746/042516401776563391
|View full text |Cite
|
Sign up to set email alerts
|

Wedge‐shaped conformation of the dorsolateral aspect of the third tarsal bone in the Thoroughbred racehorse is associated with development of slab fractures in this site

Abstract: Summary Anecdotal evidence suggested that many cases of third tarsal bone (T3) fracture encountered clinically were associated with an abnormal shape to this bone. The radiographs of 10 normal horses and 10 horses affected with slab fracture of T3 were therefore examined to ascertain if any pre‐existent radiological abnormality was present in cases of fracture. Measurement of the maximum and minimum width between the proximal and distal articular surfaces of the dorsolateral aspect of this bone was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
1
13
1
Order By: Relevance
“…Another study showed an association between wedging of the dorsolateral aspect of the third tarsal bone in yearling prepurchase films and slab fractures once the horses entered training. Another study found an association between third tarsal bone wedging and osteoarthritis formation in the proximal intertarsal, distal intertarsal and tarsometatarsal joints in skeletally mature horses of various breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an association between wedging of the dorsolateral aspect of the third tarsal bone in yearling prepurchase films and slab fractures once the horses entered training. Another study found an association between third tarsal bone wedging and osteoarthritis formation in the proximal intertarsal, distal intertarsal and tarsometatarsal joints in skeletally mature horses of various breeds.…”
Section: Discussionmentioning
confidence: 99%
“…These fractures are found more commonly in racehorses than in horses engaged in other activities (Tulamo et al 1983;Winberg 1999;Murphey et al 2000). Although these fractures have an acute presentation, there may be some predisposing factors (Dewes 1982;Murphey et al 2000;Baird and Pilsworth 2001). Immature foals may suffer from incompletely ossified tarsal bones that may lead to abnormally shaped and less dense third and central tarsal bones in adult life (Dewes 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Immature foals may suffer from incompletely ossified tarsal bones that may lead to abnormally shaped and less dense third and central tarsal bones in adult life (Dewes 1982). It has been recently reported in Thoroughbred racehorses that wedgeshaped, third tarsal bones (T3) are more likely to sustain a slab fracture than those with normally-shaped T3 (Baird and Pilsworth 2001). Tarsal slab fractures occasionally occur bilaterally (Murphey et al 2000;Elce 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Fractures were classified as displaced (>1 mm fracture gap) or nondisplaced (<1 mm fracture gap). Wedge deformity of the third tarsal bone was classified as a zone of convergence of its centrodistal and tarsometatarsal articular surfaces . Smooth proximal curvature of the dorosolateral aspect of the tarsometatarsal joint was considered a normal variant.…”
Section: Methodsmentioning
confidence: 99%
“…This repeatable configuration suggests a predisposition for fracture at this location and is considered the result of failure of adaptive remodelling in response to exercise . Others have suggested that developmental abnormalities (wedge shaped third tarsal bone) may be a predisposing factor . Fractures with monotonic aetiologies can occur with varying configurations.…”
Section: Introductionmentioning
confidence: 99%